Radiant representations: Japanese visual propaganda in Malaya and its alignment with the greater East Asia co-prosperity sphere, 1940–1945 / Chan Leong Kit - Chan , Leong Kit (2018)
This is a visual studies research on a significant historical event in the Asian region, specifically the Japanese militarist occupation across Malaya and her neighbouring regions between the years 1940 to 1945. Through visual analyses, this research investigates the ways by which Japanese visual propaganda materials during the Japanese occupation communicate their main ideology, the Greater East Asia Co-Prosperity Sphere (GEACPS) to the people of these occupied territories. This research demonstrates the reliance of the visual propaganda materials on subject matters and their representation to communicate the propaganda narratives of the GEACPS ideology. Sourced from national and independent archival organisations as well as online archival databases, the visual materials studied comprise of various forms of print materials produced during the period of occupation, including propaganda magazines, posters, leaflets, postcards, currency design and stamps. This research first identifies the different propaganda narratives under the overarching ideology of the GEACPS, and then proceeds to conduct a survey on the visual propaganda materials to understand how these propaganda narratives were communicated visually through its subject matters and their representation. To aid the analyses of the visual propaganda materials, the research will also refer to different aspects of Japanese culture and society of that period, including aspects of Japanese spirituality, gender roles and Japanese modern identity, as these aspects play a relevant role in the narratives of their propaganda ideology.